Aneurysmal subarachnoid hemorrhage: pathobiology, current treatment and future directions. (April 2015) - Serrone, Joseph C; Maekawa, Hidetsugu; Tjahjadi, Mardjono; Hernesniemi, Juha
Abstract : Aneurysmal subarachnoid hemorrhage is the most devastating form of stroke. Many pathological mechanisms ensue after cerebral aneurysm rupture, including hydrocephalus, apoptosis of endothelial cells and neurons, cerebral edema, loss of blood–brain barrier, abnormal cerebral autoregulation, microthrombosis, cortical spreading depolarization and macrovascular vasospasm. Although studied extensively through experimental and clinical trials, current treatment guidelines to prevent delayed cerebral ischemia is limited to oral nimodipine, maintenance of euvolemia, induction of hypertension if ischemic signs occur and endovascular therapy for patients with continued ischemia after induced hypertension. Future investigations will involve agents targeting vasodilation, anticoagulation, inhibition of apoptosis pathways, free radical neutralization, suppression of cortical spreading depolarization and attenuation of inflammation.